Studi Kualitas Layanan Pengiriman: Pendekatan SERVQUAL dengan Teknik CZSQ-CZIPA - Mariska Renanda; Wandhansari Sekar Jatiningrum (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
The growth of the number of companies engaged in delivery services has given rise to intensified market competition. Therefore, companies need to provide the best service quality by considering competitor performance to win market competition. This study aims to analyse the quality of delivery services based on service quality attributes in SERVQUAL and location factor. The case study was conducted at X as the focal company and Y as a competitor. The research instrument used a questionnaire containing questions related to the level of service importance and the perceived service for each company, as well as the level of desired service by consumers. A total of 100 respondents, specifically individuals utilising service provided by X and Y, were surveyed using the purposive sampling technique.. Data analysis was carried out with CZSQ-CZIPA technique to facilitate a comprehensive evaluation of the services quality provided by the company, with a particular focus on consumer desires and make service quality from competitors as a minimum limit of services provided. The results showed that there were 6 service attributes with a CZSQ value < 0, which means that consumers feel dissatisfied with the services of J&T Express. Furthermore, it was established that 16 service attributes are situated to the left of the ideal line, indicating that service quality provided by X was lower than Y. A mapping on the CZIPA matrix indicated that there were five attributes situated within quadrant A, which signifies the necessity for improvement. They are timeliness of delivery, responsiveness to complaints and information to consumers, media available for criticism and suggestions, and ease of access to agent locations. The attribute with the highest priority for improvement is timeliness of delivery. The findings of this study are expected to be reference for company to allocate its resources for improving the service quality in accordance with the identified priorities.